If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -58 = 7x + -82 Reorder the terms: -58 + 9x = 7x + -82 Reorder the terms: -58 + 9x = -82 + 7x Solving -58 + 9x = -82 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -58 + 9x + -7x = -82 + 7x + -7x Combine like terms: 9x + -7x = 2x -58 + 2x = -82 + 7x + -7x Combine like terms: 7x + -7x = 0 -58 + 2x = -82 + 0 -58 + 2x = -82 Add '58' to each side of the equation. -58 + 58 + 2x = -82 + 58 Combine like terms: -58 + 58 = 0 0 + 2x = -82 + 58 2x = -82 + 58 Combine like terms: -82 + 58 = -24 2x = -24 Divide each side by '2'. x = -12 Simplifying x = -12
| (s-12)-24=3(s+2) | | 6m=-2m+16 | | x^3-2x^2+4=0 | | 4.5*n=2.6 | | 8y-9+2y=5y-3 | | 4x^4-10x^3-55x^2-21x=0 | | (a+5)(a-5)=0 | | m^2+8m=12 | | 8x+2=2-4x | | 7x-2(x+3)=-5x-4 | | y=.88(1993) | | -0.3(0.7-0.9)=-1.83 | | 4x+3=24-8x | | -d+6=16 | | m(z)=5z^2+4 | | -7x-8+9x=-8x-2 | | y=.88(1993)-2012 | | Ifm(z)=5z^2+4 | | 3(6t-4)= | | 7x-2(x+3)=5x-4 | | X^3=3x | | 4x+y=z+24 | | 2x+40= | | 5x+x^2-6=0 | | 5(-3x)-12x= | | 8x-6y+5x= | | y^3+y^2=16y+16 | | 7x-(-9x)-15x=8 | | -80+(-16)=5x+x | | 4t-10t-11t= | | 7x+8=-63 | | -3y+9=-3y-7 |